PENGARUH PENAMBAHAN EPOKSI PRIMER TERHADAP LAJU KOROSI BAJA KARBON RENDAH YANG DIRENDAM DALAM LARUTAN KAPORIT (KALSIUM HIPOKLORIT) YANG BERSIRKULASI - Eka Putra, Ismet; Wardianto, Dedi; Aulia, Joni (ITP Press, 2023)
Chlorine solution, is usually used as a water disinfectant, which can cause metal corrosion. Circulating solution can erode the protective layer thereby accelerating corrosion. Epoxy primer provides the best rust prevention and adhesion properties compared to other types of primer. This research was conducted using 27 specimens in 3 vessels in each vessel there were 9 specimens with soaking low carbon steel without treatment, which was coated with paint and coated epoxy primary. The volume of 1 liter of chlorine solution for 1 vessel. The results of this study indicate that the primary epoxy coated can hamper corrosion well. Low carbon steel weight reduction that without treatment or which is not coated much larger than in low carbon steel coated with paint and coated epoxy primary even though the paint coated is still unable to withstand the corrosion rate well. The lowest corrosion rate with the provision of primary epoxy in a 60-day immersion time with an average value of 0,002879872mpy and the highest corrosion rate with without treatment or which is not coated with a 15-day pronounce time with the average value 0,009015251 mpy.